EFFECT OF PRIMING ON SEED VIGOR OF WHEAT (Triticum aestivum L.) - Arief, Ramlah; Koes, Fauziah; Komalasari, Oom (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2012)
Priming is a process that controls the process of hydration of seeds for the ongoing metabolic processes before germination. Research on priming was conducted at ICERI seed laboratory from May to September 2009 to evaluate the effect of different priming methods on wheat seed vigor. Physical properties and chemical composition of seed were evaluated before seeds were treated. The priming treatment were conducted by soaking 250 g of seed in 500 mL of solution for hydropriming and halopriming. Two seed lots of Nias and Dewata variety were subjected to heated and unheated distilled water for 12hours and subjected to KCl and CaCl2 at 10, 20, and 30 ppm and unprimed seed. The experiment were arranged in completely randomized design, replicated thrice. Vigor evaluation by observed seed germination, simultaneity growth, germination rate, seedling dry weight, electric conductivity of seed leakage and length of primary root. The results showed that highest germination, simultaneity growth, seedling dry weight, and length of primary root, were priming treatment with KCl 30 ppm and CaCl2 20 and 30 ppm. Priming with distilled water for 12 hours gave higher germination percentage and simultaneity growth. Keywords : priming, wheat, seed, vigor